A Review on the Effect of Cryogenic Treatment on the Mechanical Properties of Friction Stir Welded Joints - Mishra, Akshansh; Nidigonda, Gopikrishna (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
If we talk about the thermal processing of metals, it is nothing new. Heat treatment of metals dates back to thousands of years. Metal characteristics have been altered by using various heat treatment processes. But the treating the metals at the cold temperature especially at very cold temperature in the cryogenic range is relatively new and has not been accepted fully in the manufacturing industries. This paper focuses on the change of mechanical properties of Friction Stir Welded joints after cryogenic treatment process.